If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = -5 + 2x + -7y Solving 35 = -5 + 2x + -7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 35 + -2x = -5 + 2x + -2x + -7y Combine like terms: 2x + -2x = 0 35 + -2x = -5 + 0 + -7y 35 + -2x = -5 + -7y Add '-35' to each side of the equation. 35 + -35 + -2x = -5 + -35 + -7y Combine like terms: 35 + -35 = 0 0 + -2x = -5 + -35 + -7y -2x = -5 + -35 + -7y Combine like terms: -5 + -35 = -40 -2x = -40 + -7y Divide each side by '-2'. x = 20 + 3.5y Simplifying x = 20 + 3.5y
| x-30=14-(3x) | | 6x-(4x+2)=10 | | x+1=-6x | | 5w-2=-32 | | 3b^3+22b^2-80b=0 | | 4-12x=-8x | | x+x+10+x+5=180 | | 0.40m-14=9+0.60m | | -6(2y-12)=-108 | | 12n^2+54n-210=0 | | 44x^2-4x+5=4x+6 | | 6y-2-7=37 | | 6a+7=3a+1 | | h(x)=x(3)-4 | | R+7r=18 | | 268=11*80 | | Z^2+6+13=0 | | 2+n=n+2 | | -4(w-5)(-w-7)=0 | | X+10+x+x+5=180 | | 12-2b+8b=b+2 | | 12-2b+=b+2 | | 7p^2-5p-2=0 | | h(-1)=3(-1)+4 | | 2x^2-16x+64=36 | | 3x-9-8x= | | y=50-3x | | lx-6l=-7 | | 3m-16+5m=m+20+4m | | -3u(u+2)(u-8)=0 | | 10r^3+55r^2+75r=0 | | -8(v+3)+4v+5=7v+9 |